Pengaruh E-Money dan E-Commerce Terhadap Tingkat Inflasi - Siti Fatimatu Zahro (Jurnal Prospek: Pendidikan Ilmu Sosial dan Ekonomi, 2025)
This study aims to determine how the influence of inflation and investment on economic growth in Indonesia. This study is a type of descriptive research with a quantitative approach. Data collection techniques are carried out by literature study techniques. These data were obtained from journals and government websites such as BPS. The Data used is time series data in the 2018-2022 time series. Data analysis techniques used are multiple linear regression models. From the data that has been described it can be seen that both independent variables have a significant influence on economic growth but for inflation has a negative relationship while investment has a positive relationship. This is because with rising inflation, it will reduce the percentage of economic growth in Indonesia, while if the level of investment in Indonesia increases, economic growth will also increase.